LOCAL MONITORING OF CONTAMINANT EMISSION CARRYING OUT AT RUP «BMZ» - A. I. Pankovets; A. A. Kotov; N. A. Osipenko (Литьë и металлургия, 2011)
RUP «BMZ» carries out local monitoring of discharge of contaminant in atmosphere. The aim of local monitoring of environment is study and forecast of change of controlled variables of discharge from the sources of pollution, situated on the territory of the region.